Sovereign risk, interbank freezes, and aggregate fluctuations - Philipp Engler; Christoph Große Steffen (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2014)
This paper studies the bank-sovereign link in a dynamic stochastic general equilibrium set-up with strategic default on public debt. Heterogeneous banks give rise to an interbank market where government bonds are used as collateral. A default penalty arises from a breakdown of interbank intermediation that induces a credit crunch. Government borrowing under limited commitment is costly ex ante as bank funding conditions tighten when the quality of collateral drops. This lowers the penalty from an interbank freeze and feeds back into default risk. The arising amplification mechanism propagates aggregate shocks to the macroeconomy. The model is calibrated using Spanish data and is capable of reproducing key business cycle statistics alongside stylized facts during the European sovereign debt crisis.
Keywords: E43; E44; F34; H63; 330; sovereign default; interbank market; Bank-sovereign link; non-Ricardian effects; secondary markets; domestic debt; occasionally binding constraint